Memaknai Ulang Corporate Social Responsibility: Upaya Mewujudkan Fair Responsibility - Tauchid Komara Yuda (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
CSR is essentially interpreted as a manifestation of the responsibility of the business world over the externalities arising from their production activities. But unfortunately this responsibility is only limited scope primary operationalization region without regard for the fact that externalities it has started from the ﬁrst phase of extraction up to a radius of these products are marketed. Therefore, this paper seeks to encourage the existence of fair responsibility by understanding a CSR as companies att empt to produce eco-friendly products. With the company’s commitment to implement eco-friendly production methods, then indirectly the company has been reducing their externalities, its same doing CSR.